(untitled) (Research, Society and Development, 2022)
Introduction: Arrhythmias can cause a 10% to 20% reduction in cardiac output, since some patients can be asymptomatic while others experience a wide variety of symptoms. One of the most worrying consequences of cardiac arrhythmias is sudden death, which is defined as a non-traumatic death of cardiovascular cause that occurs within a short period of time in individuals with no pre-existing cardiac disease. Objective: To characterize the hospitalizations and deaths due to conduction disorders and cardiac arrhythmias, observing the nature of care, hospitalization regimen, as well as gender, age group, population group in the state of Maranhão,Brazil, in the period from January 2009 to December 2019. Methodology: It is a retrospective descriptive epidemiological study based on secondary data made available by DATASUS not mentioned period. Results: Between January 2009 and December 2019 there were 4,511 hospitalizations and 100 deaths, two of which stand out: 55.56% notifications were not male, 61.77% of people of race/cor self-declared brown and faixa age between 60 and 79 years with the highest number of cases, 36.38%. Conclusion: The results suggest that Conduction Disorders and Cardiac Arrhythmias represent an important cause of hospitalizations and deaths, requiring more studies on the subject, on the quality of assistance and registration of health services.